Regulating labor : the state and industrial relations reform in postwar France - Howell, Chris, 1962- (Princeton University Press, 1992)
In May and June of 1968 a dramatic wave of strikes paralyzed France, making industrial relations reform a key item on the government agenda. French trade unions seemed due for a golden age of growth and importance. Today, however, trade unions are weaker in France than in any other advanced capitalist country. How did such exceptional militancy give way to equally remarkable quiescence? To answer this question, Chris Howell examines the reform projects of successive French governments toward trade unions and industrial relations during the postwar era, focusing in particular on the efforts of.